Secularism on the Edge
XIII, 299 p.
Keywords: In this dynamic and wide-ranging collection of essays, prominent scholars examine the condition of church-state relations in the United States, France, and Israel. Their analyses are rooted in a wide variety of disciplines, ranging from ethnography and demography to political science, gender studies, theology, and the law.